The biology of suburban olive thrushes (Turdus olivaceus olivaceus) in the Eastern Cape, South Africa - Bonnevie, Bo Tørris (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2005)
This study investigated the biology of the Olive Thrush Turdus olivaceus olivaceus in Grahamstown, South Africa from 1998 to 2003. Behavioural differences between males and females, parent-young interactions, development of fledglings, and the role of song and moult in territorial behaviour were investigated. Comparisons of biometrics, moult and survival were made using Olive Thrush ringing data from other regions. There were no significant differences in mass, wing length or survival rate between the Eastern and Western Cape provinces, but primary wing moult started earlier in the Western Cape and coincided with the end of the main breeding periods in both provinces. Both males and females of breeding pairs remained in and defended their territories throughout the year, but there was some evidence that territorial defence was strongest during the breeding periods. Roughly, every 100 eggs laid produce 50 fledglings. Out of these 20 to 30 reach the age of independence at approximately 50 days, and only five of these juvenile birds reach maturity. Adult survival was estimated at 80%, with a mean life expectancy of 4.5 years and a conservative estimate of maximum lifespan of 11 years. Using ringing data and museum specimens, the Olive Thrush was compared with the Karoo Thrush Turdus smithi, a former race of the Olive Thrush. Olive Thrushes had shorter bills and wings, but were heavier than Karoo Thrushes from the Cradock district. There were also differences in bill and eye-ring colouration between these populations. No morphological differences were found between the sexes in either species.
Keywords: Thrushes; Turdus; Thrushes -- South Africa -- Eastern Cape; Turdus -- South Africa -- Eastern Cape